(untitled) (Foro de Educacion, 2026)
This study investigates the complex relationships among sport education, digital behaviors, and mental health in university students from China and South Asia. We developed an integrated conceptual framework grounded in Self-Determination Theory (SDT) to examine how sports enjoyment and social media addiction jointly mediate the relationship between structured sport education and psychological outcomes. We collected primary data using a cross-sectional design from a balanced multinational sample of N=612 university students (308 from China and 304 from South Asia). We evaluated the data using Partial Least Squares Structural Equation Modeling (PLS-SEM) in two stages: measurement and structural models. The results indicate lower psychological distress, though both the structural components of sport education and the intrinsic level of sports enjoyment predict this outcome differently. Sports enjoyment (β = -0.310) is a stronger predictor of reduced social media addiction than the structural components of sport education (β = -0.190). Social media addiction is an important competing factor, as it can partly reduce the mental health benefits of taking part in sports. The PLSpredict analysis shows strong predictive power, especially for psychological distress (Q2 predict up to 0.428). These findings suggest that sport education primarily helps by playing sports more enjoyable and reducing digital addiction. The study points out that educators should focus on making sports enjoyable to support mental health and digital well-being, especially in demanding academic settings where digital use is high.